Summarizing and exploring data of a decade of cytokinin-related transcriptomics - Brenner, Wolfram G.; Schmülling, Thomas (Frontiers in Plant Science, 2015)
The genome-wide transcriptional response of the model organism Arabidopsis thaliana to cytokinin has been investigated by different research groups as soon as large-scale transcriptomic techniques became affordable. Over the last ten years many transcriptomic datasets related to cytokinin have been generated using different technological platforms, some of which are published only in databases, culminating in an RNA sequencing experiment. Two approaches have been made to establish a core set of cytokinin-regulated transcripts by meta-analysis of these datasets using different preferences regarding their selection. Here we add another meta-analysis derived from an independent microarray platform (CATMA), combine all the meta-analyses available with RNAseq data in order to establish an advanced core set of cytokinin-regulated transcripts, and compare the results with the regulation of orthologous rice genes by cytokinin. We discuss the functions of some of the less known cytokinin-regulated genes indicating areas deserving further research to explore cytokinin function. Finally, we investigate the promoters of the core set of cytokinin-induced genes for the abundance and distribution of known cytokinin-responsive cis elements and identify a set of novel candidate motifs.